Actualistic Taphonomy of Small Mammals from Owl Pellets in South America and Its Archaeological Implication - Fernández, Fernando Julián (2017)
Owl predation is one of the most recurring causes of small mammal (˂1kg) accumulations in both archaeological and paleontological rock shelters, karstic system and open-air sites. The earliest actualistic taphonomic researches of small mammal remains have emerged in the 1970s and 1980s. However, it was not until the 1990s that a clear and analytical methodology was established, using small mammal species from North America, Europe and Africa. During the mid- to late 1990s actualistic taphonomic works began to be developed in South America, with exclusivity in Argentina and Chile. Since 21st century started to exponentially multiply the actualistic papers mostly of owls with a strict application of the taphonomic methodology. The useful of these studies in the archaeology (even paleontology) of South America also followed this growing tendency. However, since some years, it has been highlighting the disparity in the evidence of digestive action on different taxa. Thus, this methodology was recently re-evaluated considering the dentary morphology of rodents and marsupials from South America. The results achieved to date, added to what we intend to develop in the future will allow to obtain a higher level of detail and a better interpretation of the small mammal assemblages recovered from archaeological and paleontological sites of South America.